Increasing Public Awareness In Addressing The Impact Of Online Gambling Through Education And Guidance In Rt 01 Ulujami South Jakarta Community: MENINGKATKAN KESADARAN MASYARAKAT DALAM PENANGGULANGAN DAMPAK JUDI ONLINE MELALUI PENDIDIKAN DAN PENDAMPINGAN PADA MASYARAKAT RT 01 ULUJAMI JAKARTA SELATAN - Muzakir, Muchammad Ibnu; Rokimin (Jurnal Pengabdian Masyarakat (Bisma), 2025)
This study aims to understand the efforts to raise public awareness in tackling the impact of online gambling in Indonesia through education and counseling. The development of digital technology has led to an increase in harmful online gambling practices, both socially and economically. The research approach uses a qualitative method with case studies, in-depth interviews, Focus Group Discussions (FGD), and participatory observation in various affected communities. The results show that education plays a significant role in increasing public awareness of the risks of online gambling, particularly through character education programs, digital literacy, and community-based interventions. Counseling, both individually and in groups, has proven effective in helping individuals caught up in online gambling to recover and reduce social stigma. An inclusive approach, using both digital media and face-to-face methods, is expected to improve the effectiveness of rehabilitation and encourage greater participation in online gambling rehabilitation programs.